PENGARUH MEDIA PEMBELAJARAN VIDEO ANIMASI PADA MATA PELAJARAN IPAS KELAS V DI SD NEGERI 10 KOTO BARU - Maldin Ahmad Burhan; Yulia Darniyanti; Lutpi Ansori (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Ansori, Lutpi 2024. "The Influence of Animation Video Learning Media on the Class V Science Subject about the Water Cycle at SD Negeri 10 Koto Baru". Primary School Teacher Education Study Program. This research is motivated by science learning which is still not optimal. The learning process does not use interesting media. Therefore, many students' motivation and learning outcomes are below the minimum completeness criteria. For this reason, researchers conducted research using animated video media. The purpose of this research is to determine the effect of animated video media on the learning outcomes of IPAS students about the water cycle, at SD N 10 KOTO BARU. This type of Quasi Experimental research takes the form of a descriptive experimental method. Experimental research is a research method used to find the effect of certain treatments. The research instruments used are multiple choice questions and questionnaires for learning motivation.The data collection techniques used were pretest and posttest (final results). With the help of the SPSS 22 program using the Shapiro-Wilk test, with the criterion that if the results are significant, the results are greater than 0.05, meaning they are normally distributed. Meanwhile, if the significant result is smaller than 0.05, it means it is not normally distributed. The results of this research indicate that there is an influence of media learning animated video in class V science subjects about the water cycle at SD N 10 KOTO BARU. ,, this is proven by the posttest average.